Novel biobased epoxy resin thermosets derived from eugenol and vanillin. (February 2019) - Jiang, Hao; Sun, Lin; Zhang, Yurong; Liu, Qiqi; Ru, Chunyu; Zhang, Wanxi; Zhao, Chengji
Abstract: Novel renewable bisepoxide 2, 2′-diglycidyl ether-3, 3′-dimethoxy-5, 5′-diallydiphenylmethane (BEF-EP) and its hardener 3-methoxy-4-hydroxy-phenylbenzimidazole (VBZMI) were prepared from 1-allyl-3-methoxy-4-hydroxybenzene (eugenol) and 2-methoxy-4-formylphenol (vanillin), respectively. The chemical structures of two monomers were confirmed by their 1 H NMR spectra. Estrogenic activity test revealed that biobased bisphenol monomer 2, 2′-dihydroxy-3, 3′-dimethoxy-5, 5′-diallydiphenylmethane (BEF) as the precursor of BEF-EP showed an extremely lower estrogenic activity than commercial bisphenols (BPA and BPF). This biobased, safe and green epoxy (BEF-EP) and commercial epoxy diglycidyl ether of bisphenol F (BPF-EP) were then cured with conventional and renewable hardener (benzimidazole BZMI and 3-methoxy-4-hydroxy-phenylbenzimidazole VBZMI), respectively, for comparison. The results showed the biobased epoxy thermoset (BEF-EP/BZMI) possessed excellent thermal stability (Td5% = 372 °C), almost reaching the properties of commercial epoxy thermoset (BPF-EP/BZMI, Td5% = 385 °C). Furthermore, BEF-EP/BZMI showed good hydrophobic properties, which exhibited a higher contact angle (79.53°) than BPF-EP/BZMI (75.16°). In addition, for the comparison between VBZMI and BZMI, the epoxy resins using VBZMI as the curing agent displayed higher performance than the epoxy resins using BZMI as the curing agent. Especially, BEF-EP/VBZMI showed a higher thermal stability (Td5% = 395 °C), a higher glass transition temperature (Tg = 97 °C) and a higher contact angle (94.07) than BEF-EP/BZMI. The results could be attributed to the existence of hydroxyl groups in the side chain of VBZIMI, which enhanced the crosslinking density and then improved the rigid of epoxy material. Herein, we believe the novel biobased epoxy resin (BEF-EP) and hardener (VBZMI) has wide application as the alternative of conventional petroleum-based epoxy resin and hardener. Highlights: A novel renewable bisepoxide BEF-EP and its hardener VBZMI were prepared from eugenol and vanillin, respectively. The precursor BEF showed extremely lower estrogenic activity than commercial bisphenols. The biobased epoxy resin cured by VBZMI showed better performance than epoxy resin cured by traditional curing agent.